Urban expansion and urban policies in Rosario Metropolitan Area - Oscar Bragos (Department of Architecture Universitas Muhammadiyah Jakarta, 2017)
In this article, the growth trends in the Rosario conurbation are presented, addressing the growth of urbanized areas in the last two decades. This was a process that is characterized by:The expansive process of urbanized areas took place at a time of recovery of the country's economy and in a city that is the epicenter of a large agricultural region that produces extraordinary surplus capital. That capital surplus found in the real estate market a place where can continues to reproduce itself. To this is added the possibility of accessing mortgage credit for the construction of individual housing that generated a great demand for urbanized land. This demand did not get an answer in the city of Rosario due to the restrictive municipal urban regulation. The result: extension, dispersion and low density, the antithesis of sustainable urban development. Precisely, the article begins by exposing the main features of urban regulation in Rosario.